Microwave-assisted polymer synthesis (MAPS) as a tool in biomaterials science: How new and how powerful - Sosnik, Alejandro Dario (2011)
Lack of reproducibility, difficult and expensive scale-up and standarization of synthetic processes are the main hurdles towards the industrial production of raw synthetic and semi-synthetic polymers for (bio)pharmaceutical applications. Time- and energy-consuming synthetic pathways that usually involve the use of volatile, flammable or toxic organic solvents are apparently cost-viable and environment-friendly for the synthesis at a laboratory scale. However, they are often not viable in industrial settings especially due to the impact they have on the product cost and the deleterious effect on the environment. This has presented hurdles to the incorporation of many new biomaterials displaying novel structural features into clinics. Nevertheless, owing to unique advantages such as shorter reaction times, higher yields, limited generation of by-products and relatively easy scale-up without detrimental effects, microwave-assisted organic synthesis has become an appealing synthetic tool. Regardless of these features, the use of microwave radiation in biomaterials science has been comparatively scarce. A growing interest in the basic aspects of the synthesis of either ceramic and polymeric biomaterials has been apparent during the last decade. This article reviews the most recent and prominent applications of MW as a versatile tool to synthesize and process organic and inorganic polymeric biomaterials, and discusses the unmet goals and the perspectives for a technology that probably has the potential to make biomaterials more accessible pharmaceutical excipients and the products that involve them more affordable to patients.